Influence analysis of ownership structure on manufacturing company's performance in Indonesia 2012 - 2013 - Darwin Marasi Purba; Jhon Herlan Sianturi (The Accounting Journal of Binaniaga, 2019)
The purpose of this study is to analyse the effect of ownership structure on profitability in the manufacturing sector listed in Indonesia Stock Exchange (BEI). Independent variables used for this study consist of institutional ownership, foreign ownership, and pubic ownership. Profitability is measured by ROA (Return On Assets). While leverage as firm size is used as the control variable. This research uses secondary data, namely the annual financial statements of listed manufacturing companies in Indonesia Stock Exchange for the years 2012, and 2013. The sampling method used was purposive sampling and data analysis model used was multiple regression analysis. Results from this study indicate that institutional ownership in a company has a positive and significant effect on firm performance. Meanwhile, the foreign ownership and public ownership has no a positive effect on firm perforrmance in a company. Keyword: Ownership structure, Return on assets (ROA), Firm performance.